2019
DOI: 10.1002/ente.201800627
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide–Based Fully Spray‐Coated Inverted Solar Cells with Nontoxic Solvents: The Role of Buffer Layer Interface on Low‐Bandgap Photoactive Layer Performance

Abstract: In bulk heterojunction solar cells, the morphology of the interfaces between the photoactive layer (PAL) and charge transporting layers during the deposition process plays a key role in achieving high‐efficiency devices. Herein, an inverted fully spray‐coated solar cell fabricated on an indium tin oxide (ITO)‐glass substrate is presented. It is demonstrated that a spray‐coated double electron transporting layer composed of zinc oxide (ZnO) nanoparticles coated with polyethylenimine ethoxylated (PEIE) improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The highest μ e and μ h values with the most balanced μ e /μ h ratio for SVA-assisted one-step spraying fullerene- and nonfullerene-based devices make them exhibit the best device performance among all of the corresponding spraying OSCs (Figure ). The PCEs of conventional two-step spraying fullerene- and nonfullerene-based OSCs in previous reports are shown in Figure S14. ,,,,,, It can be found that the SVA-assisted one-step spraying technique is proposed for the first time and the obtained PCEs are comparable to those of the two-step spraying OSCs reported to date because of better PFN self-assembly, finer donor–acceptor phase separation, and smoother film morphology.…”
Section: Results and Discussionmentioning
confidence: 61%
“…The highest μ e and μ h values with the most balanced μ e /μ h ratio for SVA-assisted one-step spraying fullerene- and nonfullerene-based devices make them exhibit the best device performance among all of the corresponding spraying OSCs (Figure ). The PCEs of conventional two-step spraying fullerene- and nonfullerene-based OSCs in previous reports are shown in Figure S14. ,,,,,, It can be found that the SVA-assisted one-step spraying technique is proposed for the first time and the obtained PCEs are comparable to those of the two-step spraying OSCs reported to date because of better PFN self-assembly, finer donor–acceptor phase separation, and smoother film morphology.…”
Section: Results and Discussionmentioning
confidence: 61%
“…Spray-coating has been widely used for coating transparent conductive films in the touch panel, solar cells, etc. [301][302][303][305][306][307][308][309][310][311] For instance, Girotto et al [311] utilized the spray coating of the hole-transport layer (poly(3,4ethylenedioxythiophene):poly(styrenesulfonate)) (PEDOT:PSS), electron-transport layer (poly(3-hexyl thiophene) (P3HT):C 60derivative (6,6)-phenyl C 61 -butyric acid methyl ester (PCBM) mixture) (P3HT:PCBM) for fabricating highly efficient organic solar cells with a power conversion efficiency of 3.75%. By optimizing the ink formula, the authors were able to deposit thin films with a well-defined thickness (<10 nm) and small surface roughness.…”
Section: Spray-coatingmentioning
confidence: 99%
“…Recently, the inexpensive and flexible polymer thin films with stable inorganic nanostructures as fourth generation solar cells are developed to improve the efficiency [70]. In this regard, different indium oxide based nanomaterials are used for fabrication of advanced solar cells that can efficiently convert light energy into electricity [71,72].…”
Section: Photovoltaic Cellsmentioning
confidence: 99%